Swelling deformation and model calculation of Mg/Ca-bentonite under the influence of salt solution - Hongming Li; Youqian Lu; Hongri Zhang (PLoS ONE, 2025)
The swelling characteristics and mechanisms of bentonite are significantly influenced by the chemical environment of the pore solution, making it essential to study its behavior under different pore solutions in various engineering applications. Taking magnesium-calcium-based bentonite (Mg/Ca-bentonite) as the research object, swelling tests with different concentrations of NaCl solution were carried out to study the effect of salt solution on the deformation characteristics of bentonite. The test results show that the soil expansion rate decreases from 43.7% to 37.1% with the increase of salt solution concentration. The swelling mechanism of bentonite under the influence of NaCl solution was explained from the aspects of lattice expansion theory, diffuse double layer (DDL) theory and comprehensive factors, scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) test were introduced to further explain it from the microscopic aspect. With the increase in salt solution concentration, SEM results reveal that the soil pores become more compact and uniform. Correspondingly, the dual-peak structure observed in the MIP results transitions as the large-pore peak disappears, gradually forming a single peak within the small-pore range. Besides, the function of the swelling and time relationship curve of bentonite was fitted; the relationship model between swelling and solution concentration was established based on this, and the swelling of NaCl solution of different concentrations was simulated and verified, which provides a theoretical model basis for the practical application and numerical simulation of bentonite engineering.